Effect of biomass derived biochar materials on mechanical properties of biochar epoxy composites. (November 2021) - Minugu, Om Prakash; Gujjala, Raghavendra; Shakuntala, Ojha; Manoj, Panchal; Chowdary, M Somaiah
In the current research work an attempt is made to utilize the ecofriendly biochar materials as reinforcements in polymer composites. Biochar materials were developed from Arhar stalks and Bael shells waste biomass by pyrolysis process and studied for different characteristics. The surface morphology, crystalline structure, fixed carbon content and elemental composition of synthesized biochar materials were studied using scanning electron microscope, x-ray diffraction and proximate analysis. The results showed that the biochar (BB) produced using Bael shells are highly amorphous in nature and have high amount of elemental carbon than arhar stalk biochar (AB). Using epoxy as matrix and biochar materials as reinforcement composites were fabricated with three different filler weight fractions i.e., 2%, 4% and 6%. The composites with 4% Bael shell biochar exhibited high tensile strength, and has 183% more strength when compared with neat epoxy. Increasing the filler percentage from 4% to 6% the strength and hardness of composites reduced due to poor interfacial bonding. Morphological studies were performed on fractured surfaces of tensile tested samples by using scanning electron microscope. From thermogravimetric analysis it was found that with the inclusion of biochar materials thermal stability of composites was significantly enhanced. 4% Bael biochar composites (BBC) exhibited higher thermal resistance which left 8% residual mass.